(untitled) (Ozone Therapy Global Journal, 2016)
Treatment of patients with spinal cord injury is still an unresolved issue, due to the lack of spontaneous regeneration of damaged axons. We report the case of a patient of 12 years old with spinal cord section T2 level, which occurred eight years earlier. Management consisted of an innovative Regenerative therapeutic technique that includes homeopathic medicine, ozone therapy and therapy with autologous stem cell derived from bone marrow and adipose tissue. The result was successful, managing to regain feeling and movement, moving from one level in the ASIA Qualifier A to C (American Spinal Injury Association). This case opens new options for handling this type of spinal cord injuries